Impact of elevated temperatures on greenhouse gas emissions in rice systems: interaction with straw incorporation studies in a growth chamber experiment - Gaihre, Yam Kanta; Wassmann, Reiner; Villegas Pangga, Gina (Springer, 2013)
Two pot experiments in a “walk-in” growth chamber with controlled day and night temperatures were conducted to investigate the influence of elevated temperatures along with rice straw incorporation on methane (CH4) and nitrous oxide (N2O) emissions as well as rice yield. Elevated temperature increased GWP while decreased rice yield. This suggests that global warming may result in a double negative effect: higher emissions and lower yields.